DV-QKD coexistence with 1.6 terabit/s classical channels in free space using fiber-wireless-fiber terminals - Alia, O; Schreier, A; Wang, R; Bahrani, S; Singh, R; Faulkner, G; Rarity, J; O'Brien, D; Kanellos, GT; Nejabati, R; Simeonidou, D (Optica Publishing Group, 2022)
We experimentally demonstrate for the first time the simultaneous transmission of a COW-based DV-QKD channel and an 8×200 Gpbs 16-QAM coherent optical channels, both operating in the C-band over 2.5 m of free space enabled by Fiber-Wireless-Fiber terminals.